POLITICAL AND COMMUNICATIVE PROCESS IN THE SYSTEM „POWER – SOCIETY” - Дубас, О.П. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the article the peculiarities of political-communicational process in the system „power-society” are examined. Communicational nature of power, importance of presence of technical channels and means for political-communicational process organization, role of Mass Media as an intermediary in relationship of power and society are examined. The conclusion is made about that by consequence of new practices extension of political factors, government and society interaction became the elevation of role of communicative processes that reveal political effects of message exchange in the sphere of power and serve direct form of resources distribution and values in the political system.